Unravelling the Redox‐catalytic Behavior of Ce4+ Metal–Organic Frameworks by X‐ray Absorption Spectroscopy - Smolders, Simon; Lomachenko, Kirill A.; Bueken, Bart; Struyf, Arnaud; Bugaev, Aram L.; Atzori, Cesare; Stock, Norbert; Lamberti, Carlo; Roeffaers, Maarten B. J.; De Vos, Dirk E. (Chemphyschem, 2018)
The introduction of Ce4+ as a structural cation has been shown to be a promising route to redox active metal–organic frameworks (MOFs). However, the mechanism by which these MOFs act as redox catalysts remains unclear. Herein, we present a detailed study of the active site in [Ce6O4(OH)4]‐based MOFs such as Ce‐UiO‐66, involved in the aerobic oxidation of benzyl alcohol, chosen as a model redox reaction. X‐ray absorption spectroscopy (XAS) data confirm the reduction of up to one Ce4+ ion per Ce6 cluster with a corresponding outwards radial shift due to the larger radius of the Ce3+ cation, while not compromising the structural integrity of the framework, as evidenced by powder X‐ray diffraction. This unambiguously demonstrates the involvement of the metal node in the catalytic cycle and explains the need for 2,2,6,6‐tetramethyl‐1‐piperidinyloxy (TEMPO) as a redox mediator to bridge the gap between the one‐electron oxidation of the Ce4+/Ce3+ couple and the two‐electron alcohol oxidation. Finally, an improved catalytic system with Ce‐MOF‐808 and TEMPO was developed which outperformed all other tested Ce4+‐MOFs. Redox change in Ce MOFs: The mechanism by which hexanuclear Ce4+ metal–organic frameworks act as redox catalysts is studied by X‐ray absorption spectroscopy. Up to one Ce4+ ion per cluster can be reduced (see picture) with a corresponding outwards radial shift, while not compromising the structural integrity of the framework. This demonstrates the involvement of the metal node in the catalytic cycle and explains the need for TEMPO as redox mediator in two‐electron oxidations.